The Effect of Academic Qualification, School Facilities and Compensation on Teacher Professional Competency - Rustiana, Ade; Rahmaningtyas, Wisudani; Astuti, Malinda Listia (Dinamika Pendidikan, 2018)
This study aims to determine the effect of academic qualifications, school facilities, and compensation on the teacher professional competency. The population in this study was 68 teachers in Islamic Vocational School of Al Hikmah Mayong Jepara. This study is a population research because the population is less than 100 so that the entire population is as research sample. Data collection methods used questionnaires and documentation. The data analysis technique used multiple linear regression analysis. The results showed a positive and significant influence of academic qualifications, school facilities and compensation on teacher professional competency by 72.4%, there was a positive and significant influence of academic qualifications partially on teacher professional competency by 18.15%, there was a positive and significant influence of school facilities partially on teacher professional competency by 8.29% and there is a positive and significant influence of compensation partially on teacher professional competency of 19.54%.